Alans and Chingizid States in 13th-15th Centuries - E. V. Kaziev (Научный диалог, 2024)
The article examines the relationship between the Alans and the Mongols during the latter’s global expansion. The aim is to present the main historical narratives on this issue. Various multilingual written sources from the 13th-16th centuries were used for the research. The historical-genetic approach allowed for the presentation of relevant source information outside the context of specific studies on different aspects of the problem. As a result, Alan-Mongol relations are traced within the complex of historical events, processes, and phenomena that constituted Mongol expansion. Conclusions are drawn that the Alans, inhabiting various regions of Eurasia, were drawn into the orbit of the internal and external political life of the Mongol Empire. It is asserted that despite the severe consequences of Mongol conquest, Caucasian Alania managed to integrate into the economic and political system of the Golden Horde, while Alan settlement enclaves and districts in its western and eastern parts, as well as Alans in Mongolia and China, were assimilated. Additionally, it is shown that ally-vassal relations with the Jochids played a crucial role for the North Caucasian Alans, involving them in confrontation with Timur’s empire on the side of Khan Tokhtamysh.